Exploring the Impact of Scaffolded Written Corrective Feedback on Iranian EFL Learners’ Writing Quality: A Sociocultural Theory Study - Ehsan Abbaspour; Mahmood Reza Atai; Parviz Maftoon (Journal of Modern Research in English Language Studies)
The prevalence of Sociocultural Theory (SCT) as a major theory in SLA has spurred a considerable number of studies to investigate the various aspect of L2 acquisition through the lens of this theoretical framework. The present study aimed at investigating the impact of Scaffolded Written Corrective Feedback (WCF) on Iranian EFL learners’ writing performance in terms of fluency, accuracy, grammatical complexity, and lexical complexity. Additionally, the study sought to inquire about the Iranian EFL learners’ attitudes toward Scaffolded WCF through a series of post-interviews and a questionnaire. For this purpose, 25 students who had enrolled in a university-level writing course were conveniently sampled after a homogeneity test for the study. The pedagogical treatment the participants received throughout the study was Scaffolded WCF (i.e. a ZPD-based teacher/peer corrective feedback on their writing performance). The data obtained from the pretest, immediate posttest, and delayed posttest were analyzed using a series of ANOVA and Friedman’s tests. The findings indicated that Scaffolded WCF statistically significantly contributed to the participants’ writing performance regarding grammatical complexity, fluency, accuracy, and lexical complexity. The results obtained from the attitude questionnaire and the post-interviews also revealed that the participants held a positive attitude toward the adopted approach. The findings provide promising implications for the adoption of this approach in large classes typical of Iranian university-level writing courses.